Computer vision algorithms and diffuse inference in Matlab app designer for probable diagnosis of melanomas - Quispe Pérez, Alfonso Sebastián (2024)
This article describes the procedure for implementing a graphical user interface using the App Designer development environment and the Signal Processing Toolbox of Matlab software, to reinforce the teaching of analysis in the domain of time and frequency of periodic and typical signals used in the subject Digital Signal Processing, which belongs to the Electronic Engineering Program of the Ricardo Palma University, Lima, Peru. Likewise, said interface was developed using various components such as DropDown, Button, Knob, Axes, Slider, among others, which allowed the choice of the type of signal from a list, choice of the sampling frequency and the percentage of overlap as well as the size of the window to segment the temporary signal, and in the same way the temporal, frequency and temporal graphic representation- frequency. In this way, the source code of the implementation of the graphical interface is shared with the students in order to reinforce the teaching process during the classes taught in the Computer Laboratory of the Faculty of Engineering, allowing them to interact directly with the graphical interface and manipulate it with the interest of changing the number and type of signals or updating the parameters of digitization and frequency analysis. Finally, four simulation results are presented that correspond to the choice of different periodic signals, with or without noise and DC signal, as well as different sampling frequencies and percentage of overlap.